Optimasi Persediaan Gate Valve Dengan Membandingkan Metode Economic Order Quantity Dan Period Order Quantity Di PT.X - Khairol Asmadi; Bambang Sugito (CV. ITTC INDONESIA, 2025)
Good inventory management is very important for the smooth operation of the company. The forecasting method, Economic Order Quantity (EOQ), and Periodic Order Quantity (POQ) are several methods that can be used to optimize inventory. The forecasting method is used to predict valve requirements, while the EOQ and POQ methods are used to determine the optimal number and frequency of orders. EOQ helps determine the optimal number of orders that optimize order and storage costs, while POQ allows regular scheduling of orders. This study concluded that the Decomposition method has the smallest error value of 6.81250 in the forecasting method. The total inventory cost of the existing method is Rp 281,116,815, while the EOQ and POQ methods are Rp 26,098,084 and Rp 24,375,981, respectively. The comparison between the POQ and EOQ methods shows that the POQ method is more effective and efficient in minimizing total inventory costs. The implementation of the POQ method is expected to improve the efficiency and reliability of gate valve inventory management in the warehouse.